Validation of the Refugee Health Screener-15 for the assessment of perinatal depression among Karen and Burmese women on the Thai-Myanmar border. - Gracia Fellmeth; Emma Plugge; Mina Fazel; Prakaykaew Charunwattana; François Nosten; Raymond Fitzpatrick; Julie A Simpson; Rose McGready (PLoS ONE, 2018)
Perinatal depression is common, and left untreated can have significant and long-lasting consequences for women, their children and their families. Migrant women are at particular risk of perinatal depression as a result of a multitude of stressors experienced before, during and after migration. Identification of perinatal depression among migrant women-particularly those living in low- and middle-income regions-remains challenging, partly due to the lack of locally-validated and culturally appropriate screens tools. This study formally validates Burmese and Sgaw Karen versions of the Refugee Health Screener-15 (RHS-15) as a screening tool for perinatal depression among migrant women living on the Thai-Myanmar border. The Structured Clinical Interview for the Diagnosis of DSM-IV Disorders (SCID) was used as the gold-standard comparator. Complete results were obtained for 235 Burmese-speaking and 275 Sgaw Karen-speaking women. Despite displaying reasonable psychometric properties, a number of shortcomings associated with the RHS-15 limited its utility in this setting. The Likert-type response categories of the RHS-15 proved problematic in this low-literacy population. Combined with the relative superiority and greater ease of administration of the SCID, the RHS-15 is not recommended as the tool of choice for detecting perinatal depression in this setting.